The development of Iqra' Lampung script teaching materials for primary school levels in Bandar Lampung city - Ali Imron (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
The Lampung Provincial Government requires all primary and secondary schools to provide Lampung language lessons and introduction to Lampung script. Some students only recognize the Lampung Khaganga script, which amounts to 20 characters, while the combination of the main character and 12 characters that produces 560 syllables of the Lampung script is not yet fully understood. In fact, knowledge of Lampung script is still lacking, even some students do not understand Lampung script, it can be said that learning Lampung script at elementary school level has not been successful. This could be due to a lack of modules (teaching materials) that support learning. The research aims to develop Lampung language teaching materials in Lampung script material in the form of Iqra' Lampung script as teaching material for elementary school level. This study adopted a research and development (R&D) method proposed by Gall, Borg & Gall (2007). The work step procedure includes: 1) preliminary study, 2) product development, 3) product validation test and revision. Based on the research that has been done, it can be concluded that the teaching material (module) is feasible because the average value is 4.588 from the teacher validator and 4.446 from the lecturer validator. If it is based on a scale of 5 it can be concluded that the Iqra' Lampung script teaching material has a very good value of teachers and good grades from expert lecturers in terms of material aspects, language, presentation, the effect of teaching materials on learning strategies, and overall appearance feasibility. Modules are basically teaching materials that are systematically using language that is easily understood by students according to their level of knowledge and age so that they can learn independently or without minimal guidance from teachers.